2010
DOI: 10.1111/j.1749-6632.2010.05568.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress, sex, and neural adaptation to a changing environment: mechanisms of neuronal remodeling

Abstract: The adult brain is much more resilient and adaptable than previously believed, and adaptive structural plasticity involves growth and shrinkage of dendritic trees, turnover of synapses and limited amounts of neurogenesis in the forebrain, especially the dentate gyrus of the hippocampal formation. Stress and sex hormones help to mediate adaptive structural plasticity, which has been extensively investigated in hippocampus and to a lesser extent in prefrontal cortex and amygdala, all brain regions that are invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
227
1
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 303 publications
(241 citation statements)
references
References 268 publications
(339 reference statements)
9
227
1
4
Order By: Relevance
“…These findings are consistent with extensive evidence of chronic stress being associated with larger adult amygdala volumes as a result of hypertrophy of nerve cells in the amygdala (71).…”
Section: Discussionsupporting
confidence: 79%
“…These findings are consistent with extensive evidence of chronic stress being associated with larger adult amygdala volumes as a result of hypertrophy of nerve cells in the amygdala (71).…”
Section: Discussionsupporting
confidence: 79%
“…A meta-analysis of volumetric brain studies of PTSD revealed that exposure to trauma had a relatively greater effect on hippocampal volume in males than in females (48). Consistent with this finding, animal studies have shown that chronic stress impairs neurogenesis and causes dendritic retraction in the hippocampus, along with spatial memory deficits, to a much greater degree in adult male than in female rats (49). These sex differences in sensitivity to the effects of chronic stress may reflect, in part, the effects of estrogen, which exhibits Fig.…”
Section: Discussionsupporting
confidence: 57%
“…The full model with moderation by sex is shown in Fig. 3. a number of neuroprotective effects in the hippocampus (49,50). However, in our sample, maltreatment during childhood showed similar associations with hippocampal rs-FC in both males and females.…”
Section: Discussionmentioning
confidence: 37%
See 1 more Smart Citation
“…The hippocampus is a brain region noted for its plasticity in response to stress and sensitivity to adrenal steroid hormones (6). Acute stress enhances synaptic plasticity that is associated with improved cognition and other adaptive functions whereas chronic stress produces opposite effects mediating, in the hippocampus, spine synapse turnover, dendritic shrinkage, impaired long-term potentiation (LTP), and suppression of adult neurogenesis in the dentate gyrus (DG) (1,7). Importantly, neuroanatomical changes in response to repeated stress recover in young adult animals, based upon the restoration of dendritic length and branching and spine density (8).…”
mentioning
confidence: 99%